Utilização de farinha de chia (Salvia hispânica) na elaboração de pão sem glúten sem adição de goma e gordura - Huerta, Katira da Mota (2015)
Celiac disease is a permanent intolerance to gluten and its treatment is based in the total removal of these dietary proteins . The chia seed is highly nutritious because of the high content of protein, dietary fiber and essential fatty acids. In presence of water the seed exudes a transparent mucilaginous gel that has emulsifying properties, becoming it an excellent ingredient for use as a substitute for fats and starches in the baking industry. This work aimed to evaluate the effect chia flour (Salvia Hispanic L.) in the physical, microbiological, nutritional and sensory gluten-free breads prepared without addition of starch and fat. Chemical composition analysis were carried out at the flour and developed products. To determine the quality of the bread was developed analyzes of specific volume, mass rearing, cooking losses , water activity , texture, crust color and crumb . The count of yeasts and molds was held for five days of storage and the acceptability and purchase intent of the bread was evaluated by an affective test with 50 untrained volunteers. The chemical composition of the bread indicates that the presence of chia flour increases the nutritional value and provides the decrease in carbohydrate content . All the texture parameters were influenced by partial replacement of rice and soybean flour by chia flour. Also the color of the bread became darker and decreased the specific volume and the losses caused during cooking. Regarding sensory analysis, for bread prepared without gum , the formulation containing 2.5% of chia in replacement of rice and soy flour was the most accepted with values close to 5 score on the scale represented by " liked ". On the other hand, for bread prepared without fat all the treatments showed no significant difference for flavor and texture from the standard sample. Also, the treatment with 2.5% of chia flour showed purchase intention similar to the standard for both cases . The addition of chia flour on gluten-free breads without gum and fat resulted in a healthy food product alternative for celiac consumer. However we suggest more studies to improve the bread texture parameters.